Maternal experience and adult neurogenesis in mammals: Implications for maternal care, cognition, and mental health. Issue 7 (29th August 2018) - Medina, Joanna; Workman, Joanna L.
Abstract: The transition to motherhood encompasses physiological and behavioral adaptations essential for the initiation and maintenance of offspring care and feeding and includes widespread changes throughout the brain. The growth of new neurons occurs across the lifespan in distinct regions of mammalian brains and changes dynamically across reproductive events in female mammals. The subventricular zone (SVZ) and dentate gyrus (DG) of the hippocampus undergo high rates of neurogenesis in adulthood and are sensitive to hormonal fluctuations. Pregnancy and the postpartum period are associated with increased cell proliferation in the SVZ and interneuron survival in the olfactory bulb. In mice, peripartum prolactin signaling mediates SVZ neurogenesis and is important for enhanced olfactory recognition of offspring and maternal care. In contrast, cell proliferation and immature neuron survival decrease in the DG during the postpartum period. High baseline glucocorticoid concentrations suppress hippocampal neurogenesis, potentially representing an energetic trade‐off accompanying a reduced need for spatial navigation early postpartum. In women, hippocampal volume decline during pregnancy and partial recovery during the postpartum period could contribute to the risk of psychiatric illness. New evidence indicates that the dorsal raphe nucleus (DR) is an additional site for adult neurogenesis sensitive to reproductive experience and offspring contact. In this review, we discuss the initial and lasting impact of maternal experience on adult neurogenesis. Because neurogenesis has been implicated in a variety of psychiatric and neurodegenerative illnesses, understanding how reproductive experience alters new neuron production in maternal mammals has far‐reaching implications for women's health and wellness across the lifespan.